Ideological authorship in medical articles : how do researchers become authors in literacy practices? - Ferreira, Klara Marcondes, 1994- (2021)
Dissertação - Universidade Regional de Blumenau, Centro de Ciências da Educação, Programa de Pós-Graduação em Educação, Blumenau, 2021.